In my textbook, it says that the energy (I) of a wave, determined by the power of a wave (P) divided by area (A), is determined by the following formula:

$$I = \frac{1}{2}\rho v\omega^2A^2 = 2\pi^2 \rho vf^2A^2$$ where $\rho$ is density, $v$ is propagation speed, $\omega$ is angular speed ($\omega = 2\pi f$ and $A$ amplitude.

Can anyone show how it is like this?

  • $\begingroup$ Minor notational comment to the question(v1): Usually one uses the Greek letter omega to denote angular speed, not double-u. $\endgroup$
    – Qmechanic
    Oct 21, 2012 at 18:31
  • $\begingroup$ RRRR, did you try anything to prove this yourself? While this is not a bad question as is, it could be a lot better if you made an attempt and explained where you got stuck. $\endgroup$
    – David Z
    Oct 22, 2012 at 8:17
  • $\begingroup$ And what kind of wave is this formula for? Wave of a string, surface water waves, etc.? $\endgroup$
    – MoonKnight
    Oct 22, 2012 at 16:47

1 Answer 1


It looks like the expression for the energy of a surface water wave. Here's how it is derived - if this is not the case in question, the following should enable you to derive the relevent expression you require

A progressive wave of the surface of water can be expressed in terms of the elevation of the free surface $\eta$

$$\eta = a\sin (mx - nt),$$

where $a$ is the amplitude and the velocity is $v = n / m$. The velocity potentail for such a probagation can be written as

$$\phi = \frac{g a}{n}\frac{\cosh m(y + h)}{\cosh mh}\cos(mx - nt).$$

$y$ is the coordinate transverse to the direction of propagation. If we calculate the energy of the water between two virtical planes parralell to the direction of propogation a unit distance apart, we have, for a sinlge wave length the following expression for potential energy.

$$V = \frac{1}{2}g\rho \int^{\lambda}_{0}\eta^{2}\mathrm{d}x = \frac{1}{4}g\rho a^{2} \lambda,$$

where $\lambda = 2 \pi / m$.

The kenetic energy is given by

$$T = \frac{1}{2} \rho \int^{\lambda}_{0}\int^{0}_{-h} ((\frac{\partial \phi}{\partial x})^{2} + (\frac{\partial \phi}{\partial y})^{2})\mathrm{d}x\mathrm{d}y = -\frac{1}{2}\rho \int \phi \frac{\partial \phi}{\partial n}\mathrm{d}s,$$

where the RHS of this expression is the integral along the profile of a wavelength (this transformation should be easy to find on wikipedia), where $\partial n$ is measured along the normal to the water. This assumes we are dealing with small amplitudes we find

$$T = \frac{1}{2}\rho \int^{\lambda}_{0} (\phi \frac{\partial \phi}{\partial y})_{y = 0}\mathrm{d}x = \frac{1}{2}g \rho a^{2}\int^{\lambda}_{0} \cos^{2}(mx - nt)\mathrm{d}x,$$ $$T = \frac{1}{4}g \rho a^{2}\lambda.$$

So the total energy is $I = T + V$, so we get

$$I = T + V = \frac{1}{2}g \rho a^{2} \lambda.$$

Depending on the type of waves you want, this maybe able to be expressed in the form you have above. Alternatively, this should enable you to perform a simalar derivation for phenominon like waves on a string etc.

I hope this helps.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.